Civil participation between private and public spheres: the island sphere and fishing communities in the Azores archipelago - Neilson, Alison Laurie (2016)
This paper discusses civic participation with reference to fishing communities in the Azores archipelago, Portugal. We explore how concepts and political processes actively exclude people, and how researchers could dig deeper to find opportunities to build from diverse cultural practices of participation. Specifically, we describe examples of efforts towards participatory sustainable development as well as introduce a centuries-old highly participatory practice of sharing food. The rituals of the Cult of the Holy Spirit, based on sharing and justice, are an example of strong civic engagement rich with possibility from which to build alternatives to current forms of participation for fisheries governance. We suggest that islands offer understandings of human social interactions in ways that larger landmasses might not. This is a call for reflection on images underlying our understandings of participation and governing the sea commons, and looking more closely at islanders and their long held practices.